A late-medieval history of the ancient and biblical world. Volume 1, The text - Gillhammer, Cosima Clara (Heidelberg : Universitätsverlag Winter, 2022)
The late-fifteenth-century Middle English manuscript Oxford, Trinity College, MS 29 contains a universal history of the world, which begins with the creation and covers large swathes of biblical and ancient history up to the time of Hannibal. Compiled from diverse printed and manuscript sources by a single compiler-scribe, the text forms an intricate network of sources which provides extensive material for the study of history writing and compilation in fifteenth-century England. Only very brief excerpts from this text have previously appeared in print. The present volume contains the first complete edition of this history of the world (MET 63), together with a textual apparatus. Its companion volume (MET 64) contains a comprehensive discussion of the manuscript, its language and provenance, the source texts, and the compiler's method, as well as six illustrations, a detailed commentary, and glossary.
Sisältää bibliografisia viitteitä.
Keywords: englannin kieli; historia; keskiaika; keskienglanti; käsikirjoitukset; tekstit; Raamattu -- tekstit; 1400-luku.; 1400-talet.